A tradução de Menino de engenho: as marcas linguístico-culturais sob a perspectiva da linguística sistêmico-funcional e da teoria de tradução - Bezerra, Luciano Alves (2010)
The aim of this research is to compare parts of José Lins do Rego s Menino de Engenho with its English translation, Plantation Boy. This comparison aims at examining cultural and linguistic impositions which force the translator to keep a distance from the original text. In order to achieve this goal, we will draw on Halliday s (1985;1994) Systemic Functional Linguistics (SLF) to examine the lexico-grammatical choices in both texts. Halliday (1970) claims that in order to understand language s organization, one must examine not only the structure of a language but also its usage. Systemic Functional Linguistics (SLF) is, therefore, a theory that sees language as a semantic system whose organization is linked with its usage, that is, a relationship between language and social context (Martin, 1997). We will also draw on Aubert s (1998) technical translation procedures